Religion, work and inequality - Keister, Lisa A., 1968-; McCarthy, John; Finke, Roger, 1954- (Research in the sociology of work ;, 2012)
Work behaviours and inequality in work-based rewards are essential to financial security and general well-being. Although the benefits of receiving work-based rewards, such as income, benefits and retirement packages, are significant, they are not enjoyed uniformly. Scholars have invested considerable resources in studying the processes that lead to differential work outcomes, and we know a considerable amount about what places people in the distributions of income and wealth. However, religion is a critical determinant of these outcomes that has attracted little attention. It seems logical that a person's general approach to the world - their religious beliefs or cultural orientation - would be an important determinant of their wealth. After all, the things we consider important and our operating assumptions about how the world does work and how it should work are certain to affect the goals we pursue, our decisions about critical life events, and, ultimately, how well-off we are. This volume brings together major thinkers in the field of religion, work and inequality to explore current research and to articulate an agenda for better understanding these essential social processes.